MBKM SANTRI PROGRAM; MANIFESTATION OF STUDENT CHARACTER FORMING IN PESANTREN - Afkarina, Izza; Rahman, Kholilur; BZ, Zakiyah (Nurul Jadid University, Paiton Probolinggo, East Java, 2022)
This study aims to analyze and examine the implementation of MB-KM students in shaping the character of students with the status of students or Islamic tertiary institutions based on Islamic boarding schools, with the title